Mur Méditerranée, Louis-Philippe Dalembert (2019). Issue 1 (1st April 2021) - Dize, Nathan H.
Review of: Mur Méditerranée, Louis-Philippe Dalembert (2019)Paris: Sabine Wespieser, 329 pp., ISBN 978-2-84805-328-8, p/bk, €22